DYNAMICS OF GROSS DOMESTIC PRODUCT: СURRENT PROBLEMS OF MEASUREMENTS IN TERMS OF DIGITALIZATION OF THE ECONOMY - A. S. Abroskin; N. A. Abroskina (Вестник университета)
The relevant for Russian statistics issues of digitalization processes accounting in the construction of gross domestic product indicator have been considered. Special attention to the problem of formation of the methodological basis for digital economy measurements – the definition of its boundaries, structure and principles of accounting for this object in the system of macroeconomic indicators – has been paid. An important aspect in the analysis are problems specific to measuring the impact of digitalization processes of the Russian economy on the level and dynamics of gross domestic product. These are the problems of use in the Russian practice the industrial approach, interpretation and correctness of the estimates obtained. As an alternative, an approach based on the allocation of digital segments in the industries of the national economy and taking into account their impact on gross domestic product dynamics in accordance with the general principles of the System of National Accounts, – has been proposed.